HOW EFFECTIVE IS EMPOWERING MSMEs THROUGH BUSINESS TRAININGS? A LESSON FROM DAYA PROGRAM OF BANK BTPN - Idqan Fahmi; Fithriyyah Shalihati; Suhendi (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Bank BTPN has a unique program called Daya aiming to grow the business of its MSME customers by giving free regular and systematic business trainings. The question is how effective is the Daya program in improving the business of its MSME customers. The effectiveness is shown by comparing business performances of participating MSME customers with non-participating ones. The study had been undertaken in 12 BTPN working areas by surveying 545 numbers of participants and 111 numbers of non-participants. The results showed that the Daya program had a positive direct impact on MSMEs' business variables such as turnover, operational cost and customers' business growth index (CBGI), especially at the micro-enterprises category. Indirectly, the trainings also have a good impact on MSME's family and environment reflected by changes in household expenditure (family) and number of employees (environment). Finally, the Daya program's has improved the quality of business practices of participating MSMEs in the aspects of managing finance, marketing, sales, human resources, operations and soft-skills. Keywords: empowering MSMEs, business trainings, business variables, customers’ business growth index, micro-enterprises